PERMAINAN BAKIAK DALAM MENGEMBANGKAN SOSIAL – EMOSIONAL AUD DI TK KUMARA SANTHI - Ni Made Yuni Dwi Cahyani; Nariati, Ni Ketut Sri (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
Traditional clog games are traditional games and are a cultural heritage that can be used as a medium of play in early childhood institutions. The traditional clog game is one of the games that can help the social-emotional development of early childhood. The purpose of this study is to help develop children's motor and social-emotional skills so that they can find solutions to problems that occur in the field. The method in this study is a qualitative approach method that is descriptive because it must include the phenomena and problems experienced by researchers and how to solve them. Conducting observations with interview techniques in research that aims to gain knowledge from information in Developing Social - Emotional. This research method uses observation, pre test and post test. Which involves teachers and students from the Kumara Santhi Kindergarten Unit (SPS) totaling 3 teachers, 18 children. This research recognizes the form of emotions possessed, increases the ability to control emotions, fosters harmonious relationships and communicates well with others.